Poor Foot‑Care Behavior Significantly Increases Recurrent Diabetic Foot Ulcers Among Patients - Safitri Solehah; Nita Arisanti Yulanda; Suhaimi Fauzan; Titan Ligita; R.A Gabby Novikadarti (FORIKES, 2026)
Diabetes mellitus is a major non‑communicable disease that poses a serious global health threat across socioeconomic and national boundaries. Individuals with diabetes are at high risk of developing chronic complications, including diabetic neuropathy, which may progress to diabetic foot ulcers. Approximately 90% of patients with diabetic foot ulcers face the risk of lower‑extremity amputation. Inadequate foot‑care behavior among people with diabetes further increases the likelihood of severe complications, including recurrent foot ulcers and amputation. This study aimed to analyze the relationship between foot‑care behavior among patients with diabetes mellitus and the occurrence of recurrent diabetic foot ulcers. A quantitative cross‑sectional design was employed using accidental sampling. The sample consisted of 51 patients with recurrent diabetic foot ulcers. Descriptive analysis and Spearman’s rho correlation test were used to examine the association between foot‑care behavior and ulcer recurrence. The findings demonstrated a significant relationship between foot‑care behavior and recurrent diabetic foot ulcers, with a p‑value of (0.022) and a correlation coefficient of (–0.320). Most patients with recurrent ulcers were male (60.8%), nearly half were aged ≥65 years, and 47.1% had lived with diabetes for 1–5 years. A majority experienced two episodes of recurrent ulcers (78.4%) and exhibited poor foot‑care behavior (72.5%). Poor foot‑care behavior is significantly associated with recurrent diabetic foot ulcers. The demographic profile of affected patients indicates predominance among older males with a moderate duration of diabetes. Strengthening foot‑care practices is essential to reduce recurrence and prevent severe complications.Keywords: diabetes mellitus; diabetic foot ulcer; complications; foot care